THE TNI-POLRI COMMUNICATION STRATEGY IN INCREASING COMMUNITY AWARENESS TO ACCELERATE THE HANDLING OF COVID-19 - Muzahid Akbar Hayat; Sanusi Sanusi; Risa Dwi Ayuni; Heni Hayat (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
This study discusses the Tentara Nasional Indonesia-TNI and Kepolisian Republik Indonesia-Polri (Indonesian National Army- Police of the Republic of Indonesia) Cooperation strategy and the Jakarta Provincial Government in accelerating handling of COVID-19. This Study using the theory of Organizational Resources from George R. Terry. The aim is to describe Cooperation regulations, activity methods, readiness of human resources and the availability of infrastructure facilities in accelerating the handling of COVID-19. The method used is an observational case studies method with both quantitative and qualitative approaches (mix method) and uses SWOT and AHP for analysis. As a result, the first strategy is to create cooperation policy regulations, the second strategy is to increase public awareness of implementing Health protocols, the third strategy is to create superior human resources, and the fourth strategy is to realize the readiness of facilities and infrastructure.